2021
DOI: 10.3389/fnmol.2021.757515
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Ions Aggravate Alzheimer’s Disease Through the Aberrant Activation of Neuronal Networks, Leading to Synaptic and Cognitive Deficits

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease that is characterized by the production and deposition of β-amyloid protein (Aβ) and hyperphosphorylated tau, leading to the formation of β-amyloid plaques (APs) and neurofibrillary tangles (NFTs). Although calcium ions (Ca2+) promote the formation of APs and NFTs, no systematic review of the mechanisms by which Ca2+ affects the development and progression of AD has been published. Therefore, the current review aimed to fill the gaps between elevated Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 323 publications
(370 reference statements)
0
11
0
Order By: Relevance
“…Though it is not yet entirely understood how these toxic oligomers perform their activity [63], they have been associated with several microglial and astrocytic membrane proteins. Many of these receptors, including N-methyl-D-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, cause a fast influx of Ca 2+ , triggering inflammation [65][66][67]. In addition, Aβ can also bind the receptor for advanced glycation end products (RAGE), a surface molecule found in microglia, astrocytes, and cerebral endothelial cells, which mediates immune responses [68].…”
Section: Neuroinflammation Related To Aβmentioning
confidence: 99%
“…Though it is not yet entirely understood how these toxic oligomers perform their activity [63], they have been associated with several microglial and astrocytic membrane proteins. Many of these receptors, including N-methyl-D-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors, cause a fast influx of Ca 2+ , triggering inflammation [65][66][67]. In addition, Aβ can also bind the receptor for advanced glycation end products (RAGE), a surface molecule found in microglia, astrocytes, and cerebral endothelial cells, which mediates immune responses [68].…”
Section: Neuroinflammation Related To Aβmentioning
confidence: 99%
“…It should also be noted that mitochondrial dysfunction is closely related to aberrant calcium signaling, as mitochondria are stores of calcium in cells, and excessive calcium uptake can lead to mitochondria overload, caspase activation, and apoptosis. The major organelles that maintain calcium homeostasis in cell mitochondria and the ER also play a critical role in oxidative stress [ 74 , 75 ], neuroinflammation [ 83 , 84 ], and apoptosis [ 84 ]. Thus, alterations in the production of reactive oxygen species that can lead to ER stress should also be addressed in studies of aberrant calcium signaling.…”
Section: Neurodegeneration and Calcium Signalingmentioning
confidence: 99%
“…Obvious possible candidates include neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, Huntington's disease, and Creutzfeld-Jacob disease. The role of intracellular Ca 2+ in general and of ER Ca 2+ in particular (Ureshino et al, 2019;da Costa et al, 2020;Lim et al, 2021;Callens et al, 2021;Kovacs et al, 2021;Guan et al, 2021;Huang et al, 2022;Ge et al, 2022;Kim et al, 2022) as well as of ER stress and accumulation of misfolded proteins (da Costa et al, 2020;Guan et al, 2021;Kim et al, 2022;Ren et al, 2021;Yasmeen et al, 2022;Shacham et al, 2019;Chakraborty et al, 2005) have indeed already been demonstrated in several neurodegenerative diseases.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%